Recommendation in Decreasing Burnout on the Contract Nurses - Dewa Kadek Adi Surya Antara; Nursalam Nursalam; Ninuk Dian Kurniawati (Jurnal Ners, 2013)
Introduction: Burnout is a problem that often arises in the field of human service. Nursing profession is very susceptible in experiencing burnout related to the served work involving interpersonal interactions, as well as work environment. Area of worklife is predictor factors trigger burnout, resulting in the turnover intention. The purpose of this study was to provide recommendations in decreasing burnout on the contract nurses in the Sanglah Central Hospital.Methods: This study was an explanatory research using crosssectional approach. The population consists of the nurses at the third class ward Sanglah Central Hospital-Denpasar. Eighty one nurses were recruited as sample by proportional random sampling technique. Data were collected through questionnaires and focus group discussion (FGD), and they were analyzed by using Partial Least Square (PLS).Result: Results of this study showed that control had effect on fairness, community and reward but it had no effect on workload, workload had significant effect on emotional exhaustion, value had no effect on justice and depersonalization however it showed effect on community, reward, emotional exhaustion and decreasing personal accomplishment, emotional exhaustion had effect on depersonalization and turnover intention, depersonalization had no effect on turnover intention but it had effect on the decreasing of personal accomplishment, emotional exhaustion and decreasing personal accomplishment have effect on turnover intention of contract nurse.Conclusion: The decreasing of burnout can be done by forming personal values and reducing workload of the contract nurses. The personal values can be formed through controls of the two aspects: community and appreciation depersonalization has the most dominant influence in the burnout dimensions established by aspects of emotional exhaustion, turnover intention can be decreased by reducing the dimensions of emotional exhaustion and improving personal achievement. The decreasing burnout model can be applied in other hospitals because it provides an overview of the aspects that affect burnout and prevents the emergence of turnover intention.